2014
DOI: 10.1080/09712119.2014.928631
|View full text |Cite
|
Sign up to set email alerts
|

The effects of raising system on the lipid metabolism and meat quality traits of slow-growing chickens

Abstract: We investigated the effects of different raising systems on growth performance, lipid deposition and meat quality traits of chickens. The chickens were raised for 28 days and then randomly assigned into three raising systems with similar body weight (BW) as follows: indoor caged, indoor floor pens and free-range system. They were sacrificed and analysed after 112 days. The raising system had no significant effect on BW and daily weight gain (P > 0.05), but had a significant effect on male thigh intramuscular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
3
19
1
3
Order By: Relevance
“…Meat drip loss and shear force are important parameters that can directly affect the tenderness and juiciness of meat, with meat that has a higher drip loss value considered to be drier or tougher. In the current study, the pectoralis major and thigh muscles of birds raised under FRS conditions had lower drip loss and higher shear force than those of chickens reared under CRS conditions, which was consistent with the findings of previous studies (Li et al., ; Yang et al., ). Under FRS conditions, the greater amount of physical activity may enhance the development and density of muscle fibers in chickens, and this might be a major factor underlying the increased shear force and decreased drip loss (Vestergaard et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Meat drip loss and shear force are important parameters that can directly affect the tenderness and juiciness of meat, with meat that has a higher drip loss value considered to be drier or tougher. In the current study, the pectoralis major and thigh muscles of birds raised under FRS conditions had lower drip loss and higher shear force than those of chickens reared under CRS conditions, which was consistent with the findings of previous studies (Li et al., ; Yang et al., ). Under FRS conditions, the greater amount of physical activity may enhance the development and density of muscle fibers in chickens, and this might be a major factor underlying the increased shear force and decreased drip loss (Vestergaard et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, outdoor production systems allow selection of strains that may increase comfort and bird welfare. Many consumers prefer to buy products from chickens raised outdoors (free range) because they believe that these products have superior sensory qualities or, in other words, taste better (Yang et al 2015). This perception has been confirmed by found that an outdoor (free range) raising system improved the flavour of chicken meat.…”
Section: Introductionsupporting
confidence: 49%
“…There were no significant differences in IMF or IMP among the different production systems (P > .05), which is in agreement with previously reported results (Fanatico et al 2007;Xu et al 2012). However, some studies have reported lower IMF in free-range birds due to the effects of increased activity on energy balance and lipid metabolism (Yang et al 2009(Yang et al , 2015.…”
Section: The Effects Of Raising System On Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers found that meat from the medium-growing genotype was more tender than meat from the fast-growing genotypes and that meat of birds raised with outdoor access was less tender than of those raised indoors (Fanatico et al, 2006). Many consumers prefer to buy products from chickens raised outdoors (free range) because they believe that these products have superior sensory qualities or, in other words, taste better (Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%